Sovereign Spreads : Global Risk Aversion, Contagion or Fundamentals? - Segoviano, Miguel (IMF Working Papers; Working Paper ;, 2010)
Over the past year, euro area sovereign spreads have exhibited an unprecedented degree of volatility. This paper explores how much of these large movements reflected shifts in (i) global risk aversion (ii) country-specific risks, directly from worsening fundamentals, or indirectly from spillovers originating in other sovereigns. The analysis shows that earlier in the crisis, the surge in global risk aversion was a significant factor influencing sovereign spreads, while recently country-specific factors have started playing a more important role. The perceived source of contagion itself has changed: previously, it could be found among those sovereigns hit hard by the financial crisis, such as Austria, the Netherlands, and Ireland, whereas lately the countries putting pressure on euro area government bonds have been primarily Greece, Portugal, and Spain, as the emphasis has shifted towards short-term refinancing risk and long-term fiscal sustainability. The paper concludes that debt sustainability and appropriate management of sovereign balance sheets are necessary conditions for preventing sovereign risk from feeding back into broader financial stability concerns.